'Robinson Crusoe on a desert island'? Judicial education in Ireland, 1995–2019. (September 2022) - Howlin, Niamh; Coen, Mark; Barry, Colette; Lynch, John
Abstract: Since 2019, Irish judicial education has been undergoing major structural change. Prior to the legislative establishment of the Judicial Council in that year, formal training for judges in Ireland was almost non-existent. Innovation in this area was limited to the holding of judicial conferences that occurred annually from the mid-1990s onwards. This paper places the training of Irish judges in its international context and analyses the reflections of 22 judges on how they learned the skills of judgecraft prior to the creation of a formalised system of judicial education and training. The data demonstrates that members of the judiciary engaged in a range of largely informal learning activities and provides insights into a hitherto unexplored aspect of Irish judicial culture. The data is also of broader significance in highlighting organic and unofficial aspects of judicial education, which can be overlooked in jurisdictions with highly-developed, formalised structures for training the judiciary.